MANAJEMEN SISTEM PROTEKSI DISCHARGING BATERAI LEAD ACID METODE COULOMB COUNTING - Matalata, Hendi; Noviardi, Noviardi; Johar, Leily W (Jurnal Teknologi dan Vokasi, 2025)
Knowing the battery SoC is important in battery usage, especially in renewable energy systems, electric vehicles, portable electronic devices, and other applications that use batteries as a power source. By knowing the battery SoC, users can manage battery usage, estimate the remaining time before needing to recharge or replace it. The BMS must ensure an efficient way for charging and discharging procedures. In addition, the BMS must maintain the proper SOC so that battery life can be maximized. In this study, a BMS designed for discharging protection on a battery as an energy storage that works to provide electrical energy to an electric load in the form of an electric vehicle, in carrying out its duties the BMS controls the electrical voltage limit to turn off the active switch on the load. The battery used is a Lead-Acid 12 V / 7.2 Ah, the C-rate used to serve the load of the battery discharging process is 0.15 C then the estimated battery capacity in an empty state is 6.4 Ah (SoC = 0%). The results of the study showed that the battery discharged for 6 hours and the cut-off voltage as protection was 10.6 Volts.